EDUKASI PLATFORM BMKG UNTUK PENINGKATAN LITERASI KEBENCANAAN DIGITAL SISWA SMA - Yudha Rangga WP; Dhedy Listyawan; Jamaludin; Lina Adrianti; Ferry Yonathan; Budiman; Purnama Nugroho; Sudarno; Achmad Hindasyah (Abdi Jurnal Publikasi, 2025)
Indonesia is highly vulnerable to hydrometeorological and geological disasters, but the understanding of disaster literacy among the younger generation, especially Generation Z, shows a significant gap. The purpose of this Community Service (PKM) activity is to improve the digital disaster literacy of students at Dua Mei Ciputat High School. The intervention method used was interactive education and structured practical training on the use of the official digital platform of the Meteorology, Climatology, and Geophysics Agency (BMKG), which includes the website (www.bmkg.go.id) and the InfoBMKG mobile application. The activity approach adopted a one-group pre-test post-test design, which included socialization, lectures, scenario-based training, simulations, and quantitative evaluations of 58 students. The results showed a statistically significant improvement: 62.1% of students who stated in the pre-test that they had “never” accessed the BMKG platform transformed in the post-test to 96.5% of participants who “knew” how to access and validate official information. This activity proved effective in improving practical skills and adoption of official digital platforms, bridging the gap between students' digital exposure and the use of credible information sources. The intervention successfully addressed the core problem, which was not a lack of digital skills, but rather a lack of awareness and initial recognition of credible platforms.